1996
DOI: 10.1084/jem.183.5.1981
|View full text |Cite
|
Sign up to set email alerts
|

Vesiculo-vacuolar organelles and the regulation of venule permeability to macromolecules by vascular permeability factor, histamine, and serotonin.

Abstract: SummaryIn contrast to normal microvessels, those that supply tumors are strikingly hyperpermeable to circulating macromolecules such as plasma proteins. This leakiness is largely attributable to a tumor-secreted cytokine, vascular permeability factor (VPF). Tracer studies have shown that macromolecules cross tumor vascular endothelium by way of a recently described cytoplasmic organelle, the vesiculo-vacuolar organelle or WO (WOs are grapelike clusters of interconnected, uncoated vesicles and vacuoles). Howeve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

10
235
1
3

Year Published

1999
1999
2015
2015

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 264 publications
(249 citation statements)
references
References 17 publications
10
235
1
3
Order By: Relevance
“…We may, therefore, reasonably conclude that the caveolar channels occur everywhere in the endothelial cells and in complicated profiles associated with large invaginations in their formation in the thick region. Recent transport studies have indicated that vesicle-tubule or vesicle-vacuole structures are responsible for the macromolecular transport in tumor-associated microvascular endothelial cells Feng et al, 1999;Kohn et al, 1992) and VEGF-, histamine-or serotonin-treated venular endothelial cells (Feng et al, 1996(Feng et al, , 1999. In this study and in a previous study , we observed HRP-positive deep invaginations.…”
Section: Caveola-vesicle Transportsupporting
confidence: 75%
“…We may, therefore, reasonably conclude that the caveolar channels occur everywhere in the endothelial cells and in complicated profiles associated with large invaginations in their formation in the thick region. Recent transport studies have indicated that vesicle-tubule or vesicle-vacuole structures are responsible for the macromolecular transport in tumor-associated microvascular endothelial cells Feng et al, 1999;Kohn et al, 1992) and VEGF-, histamine-or serotonin-treated venular endothelial cells (Feng et al, 1996(Feng et al, , 1999. In this study and in a previous study , we observed HRP-positive deep invaginations.…”
Section: Caveola-vesicle Transportsupporting
confidence: 75%
“…This resulted in an increase in capillary permeability, as expected from previous work. [19][20][21][22][23] However, this did not increase gene transfer, nor did prior infusion of adenosine, a vasodilator, or changing the buffer to a nominal calcium-free Krebs-Henseleit solution, which has been demonstrated to increase gene delivery in vitro. 11 Similarly, the use of oxygenated perfluorocarbons, a blood substitute, to increase both the time the virus was in the coronary circulation and to exclude blood, did not improve gene delivery.…”
Section: Discussionmentioning
confidence: 99%
“…VVOs represent an important pathway for transcellular passage of macromolecules and fluid in response to vascular permeabilizing mediators such as VEGF-A Feng et al 1996Feng et al ,1999. They may also have a role in neutrophil diapedesis (Feng et al 1998) and may provide a substantial store of membrane that can be rapidly mobilized to the cell surface early in angiogenesis to allow the rapid expansion in cell surface area that accompanies vessel enlargement (formation of "mother" vessels) (Pettersson et al 2000;Nagy et al 2002).…”
Section: Discussionmentioning
confidence: 99%